PENGARUH PENDEKATAN AESOP’S BERBANTUAN GUIDANCE WORKSHEET TERHADAP HASIL BELAJAR SISWA (Jurnal Inovasi Pendidikan Kimia, 2013)
Learning activity will be fun and optimal when applied using an appropriate learning media. One approach that can be used by teachers in teaching is the Aesop's approach with media assisted of Guidance Worksheet. This study aimed to determine whether the use of the Aesop's approach with media assisted of Guidance Worksheet have significant effect on student learning outcomes in subject of hydrocarbons and wether it have  effectiveness after it applied on an high school student in Semarang. This study uses a real experiment design. The sampling technique used is cluster random sampling, one class was as an experimental class using the Aesop's approach with media assisted of Guidance Worksheet while one class was as a control class using conventional methods. The intake of data research were obtained through the method of documentation, testing, observation and questionnaires. The average grade of post test in experimental class is 86.80 while in control class is 80.64. Hypothesis testing obtained t count (4,858) t table (1,99), which means that an average grade of cognitive learning outcomes in experiment class was better than the control class. It can be concluded that the Aesop's approach with media assisted of Guidance Worksheet had an effect on chemistry learning outcomes of hydrocarbon subject and it increase the effectiveness of student learning.